MANAGEMENT OF WINTER CEREAL CROPS FROM SOWING TO FLOWERING – SCIENTIFIC AND ECONOMIC CONSIDERATIONS - Mihai BERCA; Valentina-Ofelia ROBESCU; Roxana HOROIAȘ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Through this paper we aimed to show that, during a vegetative cycle, winter cereal must go through a physiological process of vernalization (low temperatures), which induces and controls flowering and fruiting, also regulating the following development stages. The research objective was to establish the vernalization model on 5 wheat and 2 barley winter varieties, in difficult climatic conditions, generated by water stress, lack of cold periods, but also by some technological aspects. Own research, observations and measurements were carried out in the experimental fields with varieties from south Romania (Modelu - Calarasi county), during the period 2012-2022.It was found that there are significant differences between varieties regarding the parameters required for vernalization, the development of which is genetically coordinated by genes that produce vernalin – the hormone that induces vernalization and which, modified by demethylation, forms gibberellic acid, subsequently participating in the development of the apex, of the spikelets, of the ear, pollinating anthers and soft grains. Uneven seedbed preparation work and sowing depth also create inequalities in water access to seeds, in the achievement of germination and vernalization.